Copper particle dispersion

The copper fine particle dispersion, featuring copper nanoparticles in a polymer with specific structural units and a particular dispersion medium, addresses the challenges of bonding strength and storage stability, achieving improved performance in power devices.

JP7654880B2Active Publication Date: 2025-04-01KAO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024161607
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-04-01
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

Conventional copper fine particle dispersions face challenges in achieving high bonding strength and storage stability, particularly when used in power devices that generate significant heat during operation.

Method used

A copper fine particle dispersion containing copper nanoparticles dispersed in a polymer with specific structural units, including a monomer with a carboxy group and a polyalkylene glycol segment, and a dispersion medium comprising (poly)alkylene glycol or its derivatives, terpene alcohols, glycerin, and glycerin derivatives.

Benefits of technology

The proposed dispersion achieves improved dispersion stability, storage stability, and low-temperature sinterability and bondability, resulting in enhanced bonding strength even after storage for a certain period.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654880000001
    Figure 0007654880000001
  • Figure 0007654880000002
    Figure 0007654880000002
  • Figure 0007654880000003
    Figure 0007654880000003
Patent Text Reader

Abstract

To provide a copper particulate dispersion allowed to obtain a joined body improved in joint strength even after stored over a constant period of time, owing to the improvements in stability of dispersion and storage and in low-temperature sinter-ability and joint-ability.SOLUTION: A copper particulate dispersion contains a copper nanoparticle A dispersed with polymer B and a dispersion medium C, in which the polymer B includes a monomer-derivative constituent unit having a carboxy group and a monomer-derivative constituent unit having a poly-alkylene glycol segment, the alkylene glycol segment in the polymer B has a content of 55 mass% or more and 97 mass% or less, the polymer B has an acid value of 20 mgKOH / g or greater and 250 mgKOH / g or smaller, and the dispersion medium C contains at least one selected from a group consisting of (poly-)alkylene glycol, (poly-)alkylene glycol derivative, terpene alcohol, glycerin, and glycerin derivative. There is also provided a method of making a joined body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper particulate dispersion and a method for producing a bonded body using the copper particulate dispersion. [Background technology]

[0002] Copper has excellent electrical and thermal conductivity and is therefore widely used, for example, as a conductor wiring material, a heat transfer material, a heat exchange material, a heat dissipation material, and the like. Copper has excellent thermal conductivity and is therefore sometimes used as an alternative material to solder for joining objects to be joined.

[0003] In recent years, semiconductor devices called power devices have been widely used as power conversion and control devices for inverters and the like. Unlike integrated circuits such as memories and microprocessors, power devices are used to control high currents, and generate a large amount of heat during operation. Therefore, the solder used to mount power devices is required to have heat resistance in addition to bonding strength. However, lead-free solder, which is widely used these days, has the disadvantage of low heat resistance. Therefore, various techniques have been proposed to use copper fine particle dispersion instead of solder, apply it to the target object by various coating means, and sinter it to bond the objects to be bonded. Copper contains copper atoms in an oxidized state because the oxidation state of copper is stable at room temperature (25°C). Therefore, in order to bond the objects to be bonded using copper fine particle dispersion, it is necessary to reduce the oxidized copper atoms and sinter it to make a copper continuum.

[0004] JP 2020-053404 A (Patent Document 1) describes a copper paste containing copper powder and a liquid medium for the purpose of providing a copper paste with high bonding strength to a bonded object, wherein the liquid medium contains polyethylene glycol, the copper particles constituting the copper powder have an average primary particle size of 0.03 μm or more and 1.0 μm or less, a fatty acid having 6 to 18 carbon atoms is applied to the surface thereof, the crystallite size of the (111) plane is 50 nm or less, and the mass ratio of the copper powder in the copper paste is 50% or more and 99% or less. Furthermore, JP 2013-504692 A (Patent Document 2) describes a method for producing an aqueous dispersion of metal nanoparticles with excellent dispersibility, the method including the steps of dispersing metal nanoparticles having hydrophobic ligands on their surfaces in a hydrophobic solvent, mixing the resulting dispersion with a surface modification liquid containing a surfactant, a wetting dispersant and an aqueous solvent, mixing a ligand remover with the resulting mixed liquid to produce hydrophilic metal nanoparticles, separating the hydrophilic metal nanoparticles, and dispersing the hydrophilic metal nanoparticles in an aqueous solvent. Summary of the Invention

[0005] The present invention relates to a copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 55% by mass or more and 97% by mass or less, The acid value of the polymer B is 20 mgKOH / g or more and 250 mgKOH / g or less, The present invention relates to a copper fine particle dispersion, wherein the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycol, a (poly)alkylene glycol derivative, a terpene alcohol, glycerin, and a glycerin derivative. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Copper microparticle dispersions that have been proposed as solder replacement bonding materials have higher heat resistance than solder, but there is still room for improvement in terms of bonding strength with the objects to be bonded. In addition, conventional copper microparticle dispersions may cause defects in the bonding strength of the resulting bonded body depending on the storage period of the copper microparticle dispersion. Such copper microparticle dispersions with poor storage stability are difficult to use for mounting power devices. The copper paste described in Patent Document 1, in which copper particles treated with hydrophobic fatty acid are dispersed in hydrophilic polyethylene glycol, shows poor bonding strength in a bonded body produced after storage for one month. This is believed to be due to poor dispersion of the copper paste. Furthermore, in the aqueous dispersion of metal nanoparticles described in Patent Document 2, the wetting and dispersing agent that protected the copper particles during firing is not sufficiently removed, and therefore the resulting bonded body has poor bonding strength. Therefore, there is a demand for further improvement in the storage stability and bonding property of copper particulate dispersions. The present invention relates to a copper particulate dispersion that can provide a bonded body having improved bonding strength even after storage for a certain period of time, and a method for producing a bonded body using the copper particulate dispersion.

[0007] The present inventors have found that it is possible to provide a copper microparticle dispersion containing copper nanoparticles dispersed in a polymer and a dispersion medium, the polymer containing a constituent unit derived from a monomer having a carboxy group and a constituent unit derived from a monomer having a polyalkylene glycol segment, and the content of the polyalkylene glycol segment in the polymer and the acid value of the polymer are each within a predetermined range, thereby improving the dispersion stability, storage stability, and sinterability at low temperatures of the copper microparticle dispersion, and enabling a bonded body with improved bonding strength to be obtained even after storage for a certain period of time, and a method for producing a bonded body using the copper microparticle dispersion. That is, the present invention relates to the following [1] and [2]. [1] A copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 55% by mass or more and 97% by mass or less, The acid value of the polymer B is 20 mgKOH / g or more and 250 mgKOH / g or less, The copper fine particle dispersion, wherein the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycol, a (poly)alkylene glycol derivative, a terpene alcohol, glycerin, and a glycerin derivative. [2] A method for producing a bonded body, comprising the step of interposing the copper fine particle dispersion according to [1] above between a plurality of metal members and heating the mixture.

[0008] According to the present invention, it is possible to provide a copper particulate dispersion which can give a bonded body having improved bonding strength even after storage for a certain period of time, and a method for producing a bonded body using the copper particulate dispersion.

[0009] [Copper fine particle dispersion] The copper microparticle dispersion of the present invention is a copper microparticle dispersion containing copper nanoparticles A dispersed in polymer B, and a dispersion medium C, wherein the polymer B contains a structural unit derived from a monomer (b-1) having a carboxy group and a structural unit derived from a monomer (b-2) having a polyalkylene glycol segment, the content of the polyalkylene glycol segment in the polymer B is 55% by mass or more and 97% by mass or less, the acid value of the polymer B is 20 mg KOH / g or more and 250 mg KOH / g or less, and the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycols, (poly)alkylene glycol derivatives, terpene alcohols, glycerin, and glycerin derivatives. In this specification, "sinterability at low temperature" means that metal sintering occurs in a low-temperature nitrogen atmosphere, and is also referred to as "low-temperature sinterability." The bondability of multiple metal members in a low-temperature nitrogen atmosphere is also referred to as "low-temperature bondability." For example, the low-temperature bondability after storing a copper microparticle dispersion for one month under conditions of 25°C and 50% humidity is also referred to as "low-temperature bondability after storage." In addition, in this specification, "low temperature" means a temperature lower than the general sintering temperature (about 250 to 300°C) when a silver nanoparticle dispersion is used, and refers to a temperature range of, for example, about 100 to 230°C, and it is preferable that the sinterability and bondability are improved at a lower temperature.

[0010] According to the present invention, it is possible to obtain a bonded body having improved bonding strength even after storage for a certain period of time. Although the reason for this is not clear, it is believed to be as follows. The copper nanoparticles A contained in the copper microparticle dispersion according to the present invention are dispersed in a polymer B containing a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, and a polymer B containing at least one selected from the group consisting of (poly)alkylene glycol, (poly)alkylene glycol derivatives, terpene alcohol, glycerin and glycerin derivatives, and the dispersion stability and storage stability of the copper microparticle dispersion are improved by the synergistic effect of these polymers B and dispersion medium C. Furthermore, since the content of the polyalkylene glycol segment of the polymer B is within a predetermined range, the decomposition of the polymer B is easily caused by the copper nanoparticles A even in a low-temperature nitrogen atmosphere, and as a result, the metal microparticles are close to each other, and it is considered that the low-temperature sintering property and the low-temperature bonding property are improved. For the above reasons, it is believed that the copper microparticle dispersion of the present invention improves the dispersion stability and storage stability of the copper microparticle dispersion, as well as the low-temperature sintering property and low-temperature bondability, and therefore makes it possible to obtain a bonded body with improved bonding strength even after storage for a certain period of time.

[0011] <Copper nanoparticles A> The copper fine particle dispersion according to the present invention contains copper nanoparticles A dispersed in a polymer B (hereinafter, also referred to as "copper nanoparticles A"). The copper content in the copper nanoparticles A is preferably 95% by mass or more, more preferably 98% by mass or more, even more preferably 99% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving electrical conductivity, low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. Here, "substantially 100% by mass" means that the composition may contain unintentionally contained components, such as unavoidable impurities.

[0012] The average particle size of the copper nanoparticles A is preferably 105 nm or more, more preferably 110 nm or more, even more preferably 115 nm or more, and even more preferably 120 nm or more from the viewpoint of improving the dispersion stability of the copper microparticle dispersion, and is preferably 270 nm or less, more preferably 250 nm or less, even more preferably 240 nm or less, and even more preferably 230 nm or less from the viewpoint of improving low-temperature sintering property, low-temperature bondability, and low-temperature bondability after storage. The average particle size of the copper nanoparticles A is measured by the method described in the Examples. The average particle size of the copper nanoparticles A can be adjusted by the production conditions of the copper nanoparticles A, such as the reduced metal rate, the type and amount of the polymer B, and the reduction temperature.

[0013] The content of copper nanoparticles A in the copper microparticle dispersion according to the present invention is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and even more preferably 55% by mass or more, from the viewpoint of improving low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage, and is preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 91% by mass or less, and even more preferably 90% by mass or less, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion.

[0014] <Polymer B> The copper nanoparticles A according to the present invention are dispersed in a polymer B from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties, and low-temperature bonding properties after storage. Polymer B contains a structural unit derived from a monomer (b-1) having a carboxy group and a structural unit derived from a monomer (b-2) having a polyalkylene glycol segment, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties, and low-temperature bonding properties after storage.

[0015] Examples of the basic structure of the polymer B include vinyl polymers such as acrylic resins, styrene resins, styrene-acrylic resins, and acrylic silicone resins; and condensation polymers such as polyester and polyurethane. Among these, vinyl polymers are preferred from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage. From the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties and low-temperature bonding properties after storage, polymer B is preferably a vinyl-based polymer containing a structural unit derived from a monomer (b-1) having a carboxy group and a structural unit derived from a monomer (b-2) having a polyalkylene glycol segment. The vinyl polymer is preferably a copolymer containing a structural unit derived from a monomer (b-1) having a carboxy group and a structural unit derived from a monomer (b-2) having a polyalkylene glycol segment. When the vinyl polymer is a copolymer, the vinyl polymer may be any of a block copolymer, a random copolymer, and an alternating copolymer.

[0016] [Monomer (b-1) having a carboxy group] Examples of the monomer (b-1) include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and 2-methacryloyloxymethylsuccinic acid, and unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, and citraconic acid. The unsaturated dicarboxylic acid may be an anhydride. The monomer (b-1) may be used alone or in combination of two or more kinds. From the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties, and low-temperature bonding properties after storage, monomer (b-1) is preferably at least one selected from (meth)acrylic acid and maleic acid, more preferably (meth)acrylic acid, and even more preferably methacrylic acid. In this specification, "(meth)acrylic acid" means at least one selected from acrylic acid and methacrylic acid. The "(meth)acrylic acid" in the following description has the same meaning.

[0017] [Monomer (b-2) Having a Polyalkylene Glycol Segment] Examples of the monomer (b-2) include polyalkylene glycol (meth)acrylate, alkoxy polyalkylene glycol (meth)acrylate, phenoxy polyalkylene glycol (meth)acrylate, etc. The monomer (b-2) may be used alone or in combination of two or more. In this specification, the term "(meth)acrylate" refers to at least one selected from acrylate and methacrylate. The term "(meth)acrylate" below has the same meaning.

[0018] From the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering property, low-temperature bonding property, and low-temperature bonding property after storage, the monomer (b-2) is preferably at least one selected from polyalkylene glycol (meth)acrylate and alkoxy polyalkylene glycol (meth)acrylate, more preferably alkoxy polyalkylene glycol (meth)acrylate. From the viewpoint of the same as above, the carbon number of the alkoxy group of the alkoxy polyalkylene glycol (meth)acrylate is preferably 1 or more and 18 or less, more preferably 1 or more and 14 or less, and even more preferably 1 or more and 12 or less. Examples of the alkoxy polyalkylene glycol (meth)acrylate include methoxy polyalkylene glycol (meth)acrylate, ethoxy polyalkylene glycol (meth)acrylate, propoxy polyalkylene glycol (meth)acrylate, butoxy polyalkylene glycol (meth)acrylate, octoxy polyalkylene glycol (meth)acrylate, and lauroxy polyalkylene glycol (meth)acrylate.

[0019] The polyalkylene glycol segment of the monomer (b-2) preferably contains a unit derived from an alkylene oxide having a carbon number of 2 to 4, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. Examples of the alkylene oxide include ethylene oxide, propylene oxide, butylene oxide, etc., and are preferably at least one selected from ethylene oxide and propylene oxide, and more preferably ethylene oxide. The number of alkylene oxide-derived units in the polyalkylene glycol segment is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage, and is preferably 100 or less, more preferably 70 or less, even more preferably 50 or less, even more preferably 40 or less, and even more preferably 35 or less. The polyalkylene glycol segment may be a copolymer containing units derived from ethylene oxide and units derived from propylene oxide from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties, and low-temperature bonding properties after storage. The copolymer containing units derived from ethylene oxide and units derived from propylene oxide may be any of a block copolymer, a random copolymer, and an alternating copolymer.

[0020] Specific examples of commercially available monomers (b-2) include NK Ester AM-90G, AM-130G, AMP-20GY, NK Ester M-20G, 40G, 90G, and 230G, manufactured by Shin-Nakamura Chemical Co., Ltd.; Blenmer PE-90, 200, and 350, Blenmer PME-100, 200, 400, 1000, and 4000, Blenmer PP-500, 500D, 800, 1000, and 2000D, Blenmer AP-150, 400, and 550, Blenmer 50PEP-300, 50POEP-800B, 43PAPE-600B, and PLE-1300, manufactured by NOF Corporation.

[0021] [Hydrophobic monomer (b-3)] From the viewpoint of improving low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage, polymer B may contain a structural unit derived from a hydrophobic monomer (b-3). In this specification, the term "hydrophobic monomer" refers to a monomer that dissolves in an amount of less than 10 g when dissolved to saturation in 100 g of ion-exchanged water at 25° C. The amount of the monomer (b-3) that dissolves is preferably 5 g or less, more preferably 1 g or less, from the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. The monomer (b-3) is preferably at least one selected from aromatic group-containing monomers and (meth)acrylates having a hydrocarbon group derived from an aliphatic alcohol.

[0022] From the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage, the aromatic group-containing monomer is preferably a vinyl monomer having an aromatic group with 6 to 22 carbon atoms, which may have a substituent containing a hetero atom, and more preferably one or more selected from a styrene-based monomer and an aromatic group-containing (meth)acrylate. The molecular weight of the aromatic group-containing monomer is preferably less than 500. Examples of styrene-based monomers include styrene, α-methylstyrene, 2-methylstyrene, 4-vinyltoluene (4-methylstyrene), and divinylbenzene. From the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage, styrene and α-methylstyrene are preferred. As the aromatic group-containing (meth)acrylate, from the viewpoint of improving low-temperature sintering property, low-temperature bondability, and low-temperature bondability after storage, phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, etc. are preferred, and benzyl (meth)acrylate is more preferred.

[0023] From the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage, the (meth)acrylate having a hydrocarbon group derived from an aliphatic alcohol preferably has a hydrocarbon group derived from an aliphatic alcohol having 1 to 22 carbon atoms, more preferably has a hydrocarbon group derived from an aliphatic alcohol having 1 to 12 carbon atoms, even more preferably has a hydrocarbon group derived from an aliphatic alcohol having 1 to 8 carbon atoms, and still more preferably has a hydrocarbon group derived from an aliphatic alcohol having 1 to 4 carbon atoms. Examples of the (meth)acrylate having a linear alkyl group include a (meth)acrylate having a branched alkyl group and a (meth)acrylate having an alicyclic alkyl group. Examples of (meth)acrylates having a linear alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. Examples of (meth)acrylates having a branched alkyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, isododecyl (meth)acrylate, isostearyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. An example of the (meth)acrylate having an alicyclic alkyl group is cyclohexyl (meth)acrylate. The monomer (b-3) may be used alone or in combination of two or more kinds.

[0024] From the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage, the monomer (b-3) is preferably at least one selected from an aromatic group-containing monomer and a (meth)acrylate having a linear alkyl group, more preferably at least one selected from a styrene-based monomer and a (meth)acrylate having a linear alkyl group having 1 to 4 carbon atoms, even more preferably at least one selected from styrene, α-methylstyrene, 2-methylstyrene, 4-vinyltoluene (4-methylstyrene), methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, even more preferably at least one selected from styrene, α-methylstyrene, and methyl (meth)acrylate, and even more preferably at least one selected from styrene and methyl (meth)acrylate.

[0025] From the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bonding properties, and low-temperature bonding properties after storage, polymer B is preferably a vinyl-based polymer containing, as monomer (b-1), a structural unit derived from at least one selected from (meth)acrylic acid and maleic acid, and, as monomer (b-2), a structural unit derived from an alkoxypolyalkylene glycol (meth)acrylate.

[0026] The content of the vinyl-based polymer containing the monomer (b-1)-derived structural unit and the monomer (b-2)-derived structural unit in the polymer B is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the low-temperature sintering property, the low-temperature bonding property, and the low-temperature bonding property after storage. Here, "substantially 100% by mass" means that it may contain components that are unintentionally contained. Examples of the components that are unintentionally contained include polymer B other than the vinyl polymer contained in the polymer B.

[0027] When the polymer B is a vinyl-based polymer containing a structural unit derived from a monomer (b-1) and a structural unit derived from a monomer (b-2), the total content of the monomer (b-1) and the monomer (b-2) in the raw material monomer during the production of the polymer B, or the total content of the structural unit derived from the monomer (b-1) and the structural unit derived from the monomer (b-2) in the polymer B, is preferably 72% by mass or more, more preferably 88% by mass or more, even more preferably 91% by mass or more, even more preferably 97% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the low-temperature sintering property, the low-temperature bondability, and the low-temperature bondability after storage. Here, "substantially 100% by mass" means that it may contain components that are unintentionally contained. Examples of the components that are unintentionally contained include monomers other than the monomer (b-1) and the monomer (b-2) contained in the raw material monomer (b-1) and monomer (b-2).

[0028] When polymer B is a vinyl polymer containing a structural unit derived from monomer (b-1) and a structural unit derived from monomer (b-2), the content of monomer (b-1) in the raw monomers or the content of the structural unit derived from monomer (b-1) in polymer B during the production of polymer B is, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering property, low-temperature bondability, and low-temperature bondability after storage, preferably 3 mass% or more, more preferably 5 mass% or more, and preferably 35 mass% or less, more preferably 25 mass% or more, even more preferably 18 mass% or less, and even more preferably 10 mass% or less.

[0029] When polymer B is a vinyl polymer containing a structural unit derived from monomer (b-1) and a structural unit derived from monomer (b-2), the content of monomer (b-2) in the raw monomers during the production of polymer B or the content of the structural unit derived from monomer (b-2) in polymer B is, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage, preferably 55% by mass or more, more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 84% by mass or more, even more preferably 90% by mass or more, and preferably 97% by mass or less, more preferably 95% by mass or less.

[0030] The content of polyalkylene glycol segments in polymer B is 55% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 84% by mass or more, from the viewpoint of improving low-temperature sintering ability, low-temperature bondability and low-temperature bondability after storage, and is 97% by mass or less, preferably 94% by mass or less, and more preferably 92% by mass or less, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion.

[0031] The number average molecular weight Mn of polymer B is preferably 4,000 or more, more preferably 6,000 or more, and even more preferably 7,000 or more from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 50,000 or less, more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 10,000 or less from the viewpoint of improving the dispersion stability, low-temperature bondability and low-temperature bondability after storage of the copper microparticle dispersion. The number average molecular weight Mn is measured by the method described in the Examples.

[0032] The acid value of polymer B is 20 mgKOH / g or more, preferably 25 mgKOH / g or more, more preferably 30 mgKOH / g or more, even more preferably 35 mgKOH / g or more, and even more preferably 40 mgKOH / g or more, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is 250 mgKOH / g or less, preferably 230 mgKOH / g or less, more preferably 220 mgKOH / g or less, and even more preferably 215 mgKOH / g or less, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion. The acid value of Polymer B can be measured by the method described in the Examples, but can also be calculated from the mass ratio of the constituent monomers.

[0033] The content of polymer B in the copper microparticle dispersion of the present invention is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.3 mass% or more, and even more preferably 0.4 mass% or more, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 10 mass% or less, more preferably 9 mass% or less, even more preferably 8 mass% or less, and even more preferably 7 mass% or less, from the viewpoint of improving low-temperature sintering property, low-temperature bondability and low-temperature bondability after storage.

[0034] The mass ratio of the content of polymer B to the total content of copper nanoparticles A and polymer B in the copper microparticle dispersion according to the present invention [polymer B / (copper nanoparticles A+polymer B)] (hereinafter also referred to as "polymer mass ratio") is preferably 0.0055 or more, more preferably 0.0058 or more, and even more preferably 0.0060 or more, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 0.025 or less, more preferably 0.022 or less, even more preferably 0.020 or less, and even more preferably 0.018 or less, from the viewpoint of improving low-temperature sintering property, low-temperature bondability, and low-temperature bondability after storage. The polymer mass ratio is calculated from the content of copper nanoparticles A and the content of polymer B in the copper microparticle dispersion measured by a thermogravimetric and differential thermal analyzer (TG / DTA) according to the method described in the Examples.

[0035] <Dispersion medium C> The copper microparticle dispersion of the present invention contains a dispersion medium C containing at least one selected from the group consisting of (poly)alkylene glycols, (poly)alkylene glycol derivatives, terpene alcohols, glycerin (boiling point: 290°C, molecular weight: 92) and glycerin derivatives, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bonding properties after storage of the copper microparticle dispersion.

[0036] Examples of (poly)alkylene glycols include ethylene glycol (boiling point: 197° C., molecular weight: 62), propylene glycol (boiling point: 188° C., molecular weight: 76), diethylene glycol (boiling point: 244° C., molecular weight: 106), triethylene glycol (boiling point: 287° C., molecular weight: 150), tetraethylene glycol (boiling point: 327° C., molecular weight: 194), dipropylene glycol (boiling point: 232° C., molecular weight: 134), and tripropylene glycol (boiling point: 273° C., molecular weight: 192). , tetrapropylene glycol (boiling point: 300°C or higher, molecular weight: 250), polyethylene glycol (number average molecular weight preferably 100 or more and 1000 or less, more preferably 150 or more and 600 or less, and even more preferably 180 or more and 500 or less), polypropylene glycol (number average molecular weight preferably 150 or more and 1000 or less, more preferably 180 or more and 600 or less, and even more preferably 200 or more and 500 or less), 2-ethyl-1,3-hexanediol (244°C, molecular weight: 146), and the like.

[0037] Examples of the (poly)alkylene glycol derivative include compounds in which the terminal hydroxyl groups of the (poly)alkylene glycols are etherified or esterified. Examples of the compound in which the hydroxy groups at both ends of the polyalkylene glycol are etherified or esterified include diethylene glycol dimethyl ether (boiling point: 162°C, molecular weight: 134), diethylene glycol dibutyl ether (boiling point: 254°C, molecular weight: 218), triethylene glycol dimethyl ether (boiling point: 216°C, molecular weight: 178), diethylene glycol monoethyl ether acetate (boiling point: 217°C, molecular weight: 176), diethylene glycol monobutyl ether acetate (boiling point: 247°C, molecular weight: 204), and the like. Examples of the polyalkylene glycol compound in which the hydroxy group at one end is etherified or esterified include diethylene glycol monoethyl ether (boiling point: 202°C, molecular weight: 134), diethylene glycol monobutyl ether (boiling point: 231°C, molecular weight: 162), and the like.

[0038] Examples of terpene alcohols include monoterpene alcohols such as α-terpineol (boiling point: 219°C, molecular weight: 154), linalool (boiling point: 198°C, molecular weight: 154), geraniol (boiling point: 229°C, molecular weight: 154), and citronellol (boiling point: 225°C, molecular weight: 156).

[0039] The glycerin derivative is not particularly limited as long as it is a solvent containing a structure derived from glycerin, and examples thereof include ether derivatives of glycerin, ester derivatives of glycerin, polyglycerin, and alkylene oxide adducts of glycerin (e.g., ethylene oxide adducts and propylene oxide adducts). Examples of polyglycerin include diglycerin and triglycerin, and examples of commercially available polyglycerin include polyglycerin #310, polyglycerin #500, and polyglycerin #750 manufactured by Sakamoto Yakuhin Kogyo Co., Ltd. Examples of ether derivatives of glycerin include 3-(2-ethylhexyloxy)-1,2-propanediol (boiling point: 325°C, molecular weight: 204), and the like. Examples of ester derivatives of glycerin include glyceryl tributyrate (boiling point: 305°C, molecular weight: 302), and the like.

[0040] From the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bonding properties of the copper microparticle dispersion after storage, the dispersion medium C preferably contains at least one selected from the group consisting of (poly)alkylene glycol, (poly)alkylene glycol derivatives and terpene alcohols, more preferably contains at least one selected from dipropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight preferably 100 or more and 1000 or less, more preferably 150 or more and 600 or less, even more preferably 180 or more and 500 or less), α-terpineol, diethylene glycol monobutyl ether, and even more preferably contains at least one selected from dipropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight 180 or more and 500 or less), α-terpineol, diethylene glycol monobutyl ether.

[0041] The boiling point of the dispersion medium C at 1 atmosphere is preferably 180° C. or higher, more preferably 200° C. or higher, even more preferably 210° C. or higher, and even more preferably 215° C. or higher from the viewpoint of improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 400° C. or lower, more preferably 360° C. or lower, even more preferably 330° C. or lower, and even more preferably 300° C. or lower from the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. When two or more types of dispersion medium C are used in combination, the boiling point of the dispersion medium C is a weighted average value weighted by the content (mass%) of each dispersion medium.

[0042] From the viewpoint of improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, the molecular weight of the dispersion medium C is preferably 60 or more, more preferably 100 or more, even more preferably 130 or more, and even more preferably 150 or more, and from the viewpoint of improving low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage, it is preferably 600 or less, more preferably 450 or less, even more preferably 400 or less, even more preferably 350 or less, and even more preferably 300 or less. When two or more types of dispersion medium C are used in combination, the molecular weight of the dispersion medium C is a weighted average value weighted by the content (mass%) of each dispersion medium.

[0043] The total content of (poly)alkylene glycol, (poly)alkylene glycol derivative, terpene alcohol, glycerin and glycerin derivative (hereinafter also referred to as "dispersion medium C1") in the dispersion medium C is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, even more preferably 99% by mass or more, even more preferably 99.9% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving the storage stability of the copper microparticle dispersion and the low-temperature bonding property after storage. Here, "substantially 100% by mass" means that it may contain components that are unintentionally contained. Examples of components that are unintentionally contained include dispersion medium C other than the dispersion medium C1 contained in the dispersion medium C1.

[0044] The total content of (poly)alkylene glycol, (poly)alkylene glycol derivative and terpene alcohol (hereinafter also referred to as "dispersion medium C2") in the dispersion medium C is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, even more preferably 99% by mass or more, even more preferably 99.9% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving the storage stability of the copper microparticle dispersion and the low-temperature bonding property after storage. Here, "substantially 100% by mass" means that it may contain components that are unintentionally contained. Examples of components that are unintentionally contained include dispersion medium C other than the dispersion medium C2 contained in the dispersion medium C2.

[0045] The total content of dipropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight 180 to 500), α-terpineol, and diethylene glycol monobutyl ether (hereinafter also referred to as "dispersion medium C3") in the dispersion medium C is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, even more preferably 99% by mass or more, even more preferably 99.9% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving the storage stability of the copper microparticle dispersion and the low-temperature bonding property after storage. Here, "substantially 100% by mass" means that it may contain components that are unintentionally contained. Examples of components that are unintentionally contained include dispersion medium C other than the dispersion medium C3 contained in the dispersion medium C3.

[0046] The content of dispersion medium C in the copper microparticle dispersion of the present invention is preferably 4 mass% or more, more preferably 6 mass% or more, even more preferably 7 mass% or more, and even more preferably 8 mass% or more, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 60 mass% or less, more preferably 40 mass% or less, even more preferably 20 mass% or less, and even more preferably 15 mass% or less, from the viewpoint of improving the electrical conductivity, low-temperature sinterability, low-temperature bondability and low-temperature bondability after storage.

[0047] The water content in the copper microparticle dispersion of the present invention is preferably 5 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, and even more preferably 0.01 mass% or less, from the viewpoint of suppressing copper oxidation and improving the storage stability and low-temperature bonding properties of the copper microparticle dispersion after storage.

[0048] <Copper microparticles> The copper microparticle dispersion according to the present invention may further contain copper microparticles from the viewpoint of improving electrical conductivity, low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. The copper content in the copper microparticles is preferably 95% by mass or more, more preferably 98% by mass or more, even more preferably 99% by mass or more, and even more preferably substantially 100% by mass, from the viewpoint of improving electrical conductivity, low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage. Here, "substantially 100% by mass" means that the composition may contain unintentionally contained components, such as unavoidable impurities.

[0049] The average particle size of the copper microparticles is preferably more than 0.27 μm, more preferably 0.5 μm or more, even more preferably 0.6 μm or more, and even more preferably 0.7 μm or more, from the viewpoint of improving electrical conductivity, low-temperature sintering properties, low-temperature bondability, and low-temperature bondability after storage; and from the viewpoint of improving the dispersion stability and storage stability of the copper microparticle dispersion, and the low-temperature bondability after storage, the average particle size is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less, and even more preferably 6 μm or less. The average particle size of the copper microparticles is measured by the method described in the Examples.

[0050] The content of copper microparticles in the copper microparticle dispersion of the present invention is preferably 5 mass% or more, more preferably 15 mass% or more, even more preferably 20 mass% or more, and even more preferably 25 mass% or more, from the viewpoint of improving electrical conductivity, low-temperature sinterability, low-temperature bondability and low-temperature bondability after storage, and is preferably 65 mass% or less, more preferably 55 mass% or less, even more preferably 45 mass% or less, and even more preferably 35 mass% or less, from the viewpoint of improving electrical conductivity, dispersion stability of the copper microparticle dispersion, storage stability of the copper microparticle dispersion, low-temperature sinterability, low-temperature bondability and low-temperature bondability after storage.

[0051] The mass ratio of the content of copper nanoparticles A to the total content of copper nanoparticles A and copper microparticles in the copper microparticle dispersion according to the present invention [copper nanoparticles A / (copper nanoparticles A+copper microparticles)] is preferably 0.3 or more, more preferably 0.4 or more, even more preferably 0.5 or more, and even more preferably 0.6 or more, from the viewpoint of improving the electrical conductivity, low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage of the copper microparticle dispersion, and is preferably 1.0 or less, more preferably 0.9 or less, even more preferably 0.8 or less, and even more preferably 0.75 or less, from the viewpoint of improving the electrical conductivity, low-temperature sinterability, low-temperature bondability, and low-temperature bondability after storage.

[0052] (Composition of copper particle dispersion) In the copper microparticle dispersion of the present invention, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion, the storage stability of the copper microparticle dispersion, the electrical conductivity, the low-temperature sinterability, the low-temperature bondability, and the low-temperature bondability after storage, the content of copper nanoparticles A is preferably 30% by mass or more and 95% by mass or less, the content of polymer B is preferably 0.1% by mass or more and 10% by mass or less, the content of dispersion medium C is preferably 4% by mass or more and 60% by mass or less, and the content of copper microparticles is preferably 0% by mass or more and 65% by mass or less.

[0053] The copper microparticle dispersion according to the present invention may contain various additives as components other than the above components, as long as the effects of the present invention are not impaired. Examples of the additives include metal particles other than copper nanoparticles A and copper microparticles, sintering accelerators such as glass frit, antioxidants, viscosity adjusters, pH adjusters, buffers, defoamers, leveling agents, volatilization inhibitors, etc. Examples of metal particles other than copper nanoparticles A and copper microparticles include metal particles such as zinc, nickel, silver, gold, palladium, and platinum. The content of the additive in the copper fine particle dispersion according to the present invention is preferably 1 mass % or less.

[0054] (Production of copper fine particle dispersion) The copper microparticle dispersion according to the present invention can be obtained by a method of adding and mixing a polymer B and a dispersion medium C, and if necessary, copper microparticles and various additives, to copper nanoparticles A prepared in advance by a known method; a method of mixing a copper raw material compound, a reducing agent, and a polymer B as a dispersant, and if necessary, a solvent for dispersing the copper raw material compound and the reducing agent, reducing the copper raw material compound to obtain a dispersion of copper nanoparticles A, and then adding and mixing the dispersion medium C and, if necessary, copper microparticles and various additives. Among them, from the viewpoint of improving the dispersion stability of the copper microparticle dispersion and improving the storage stability and low-temperature bonding property after storage of the copper microparticle dispersion, a method of obtaining a dried powder of copper nanoparticles A containing polymer B in advance (hereinafter also referred to as "copper nanoparticle dried powder") and then adding and mixing the dispersion medium C and, if necessary, copper microparticles and various additives is preferable. The copper nanoparticle dry powder can be obtained by mixing a copper raw material compound, a reducing agent, and a polymer B, reducing the copper raw material compound with the reducing agent, obtaining a dispersion of copper nanoparticles A dispersed in the polymer B, and then drying the dispersion of copper nanoparticles A by freeze-drying or the like.

[0055] There are no particular limitations on the copper source compound, so long as it is a compound containing copper. Examples of the copper source compound include copper sulfate, copper nitrate, cupric oxide, cuprous oxide, copper formate, copper acetate, copper oxalate, etc. The copper source compound can be used alone or in combination of two or more.

[0056] The reducing agent is not particularly limited as long as it is a compound capable of reducing the copper raw material compound. Examples of the reducing agent include hydrazine compounds such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate; boron compounds such as sodium borohydride; and inorganic acid salts such as sodium sulfite, sodium hydrogen sulfite, sodium thiosulfate, sodium nitrite, sodium hyponitrite, phosphorous acid, sodium phosphite, hypophosphorous acid, and sodium hypophosphite. The reducing agent may be used alone or in combination of two or more kinds.

[0057] Examples of the solvent in which the copper source compound and the reducing agent are dispersed include water, methanol, ethanol, propanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol.

[0058] The temperature of the reduction reaction is preferably 5° C. or higher, more preferably 10° C. or higher, more preferably 20° C. or higher, and more preferably 30° C. or higher, from the viewpoint of reducing and uniformly dispersing the copper nanoparticles A, and is preferably 100° C. or lower, more preferably 80° C. or lower, more preferably 60° C. or lower, and more preferably 50° C. or lower, from the viewpoint of stably producing copper nanoparticles. The reduction reaction may be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen gas.

[0059] In producing a copper microparticle dispersion, the dispersion of copper nanoparticles A may be purified before freeze-drying in order to remove impurities such as unreacted reducing agent and excess polymer B that does not contribute to the dispersion of copper nanoparticles A. The method for purifying the dispersion of copper nanoparticles A is not particularly limited, and includes membrane treatment such as dialysis and ultrafiltration; centrifugation treatment, etc. Among them, from the viewpoint of efficiently removing impurities, membrane treatment is preferred, and dialysis is more preferred. As the material of the dialysis membrane used for dialysis, regenerated cellulose is preferred. From the viewpoint of efficiently removing impurities, the molecular weight cutoff of the dialysis membrane is preferably 1,000 or more, more preferably 5,000 or more, even more preferably 10,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less. The copper fine particle dispersion according to the present invention can be obtained by further adding the above-mentioned various additives as necessary and performing a filtration treatment using a filter or the like.

[0060] The copper microparticle dispersion according to the present invention has good low-temperature sintering property, low-temperature bonding property, and low-temperature bonding property after storage, and therefore can be used to form conductive members of various electronic and electrical devices. The conductive members are preferably used for bonding agents such as solder; antennas such as RFID (radio frequency identifier) ​​tags; capacitors such as MLCC (multilayer ceramic capacitors); electronic paper; image display devices such as liquid crystal displays and organic EL displays; organic EL elements; organic transistors; wiring boards such as printed wiring boards and flexible wiring boards; organic solar cells; sensors such as flexible sensors, etc. Among these, the copper microparticle dispersion according to the present invention is preferably used for bonding multiple metal members from the viewpoints of low-temperature sintering property, low-temperature bonding property, and low-temperature bonding property after storage.

[0061] [Method of manufacturing the bonded body] A method for producing a bonded body according to the present invention includes a step of interposing a copper particulate dispersion between a plurality of metal members and heating the resulting mixture, wherein the copper particulate dispersion is the copper particulate dispersion of the present invention described above. When the copper particulate dispersion according to the present invention is used for bonding a plurality of metal members, it is preferable to use the copper particulate dispersion in a method for producing a bonded body, the method including a step of interposing the copper particulate dispersion between the plurality of metal members and heating the mixture.

[0062] The temperature of the heat treatment in the heating step is preferably 100°C or higher, more preferably 150°C or higher, and even more preferably 180°C or higher from the viewpoints of bonding strength and electrical conductivity, and is preferably 230°C or lower, more preferably 220°C or lower, even more preferably 210°C or lower, and even more preferably 200°C or lower from the viewpoints of improving low-temperature sinterability and low-temperature bondability. The heat treatment in the heating step can be performed either without pressure or under pressure, but is preferably performed under pressure from the viewpoint of bonding strength and electrical conductivity. The pressure of the heat treatment in the heating step is preferably 5 MPa or more, more preferably 8 MPa or more, even more preferably 10 MPa or more, and even more preferably 15 MPa or more from the viewpoint of improving low-temperature sinterability and low-temperature bondability, and is preferably 50 MPa or less, more preferably 30 MPa or less, and even more preferably 20 MPa or less from the viewpoint of productivity. The heat treatment time in the heating step can be appropriately adjusted depending on the temperature and pressure of the heat treatment. The atmosphere in the heating step may be an air atmosphere, an inert gas atmosphere such as nitrogen gas, or a reducing gas atmosphere such as hydrogen gas. From the viewpoints of inhibiting oxidation of copper and safety, a nitrogen gas atmosphere is more preferable.

[0063] Examples of metal members to be joined in the present invention include metal-based or metal substrates such as gold substrates, gold-plated substrates, silver substrates, silver-plated metal substrates, copper substrates, palladium substrates, palladium-plated metal substrates, platinum substrates, platinum-plated metal substrates, aluminum substrates, nickel substrates, nickel-plated metal substrates, tin substrates, and tin-plated metal substrates; metal parts such as electrodes of electrically insulating substrates; etc. The multiple metal members used in the present invention may be the same type of metal members or different types of metal members. Among these, the metal member preferably includes at least one selected from a gold substrate, a gold-plated substrate, a silver substrate, a silver-plated metal substrate, a copper substrate, a palladium substrate, a palladium-plated metal substrate, a platinum substrate, a platinum-plated metal substrate, an aluminum substrate, a nickel substrate, a nickel-plated metal substrate, a tin substrate, a tin-plated metal substrate, and a metal portion of an electrically insulating substrate. The joining of metal members in the present invention can be used for joining chip components such as capacitors and resistors to circuit boards; joining semiconductor chips such as memories, diodes, transistors, ICs and CPUs to lead frames or circuit boards; joining high-heat-generating semiconductor chips to cooling plates, etc.

[0064] Methods for applying the copper microparticle dispersion to metal components include various coating methods such as slot die coating, dip coating, spray coating, spin coating, doctor blading, knife edge coating, and bar coating; and various patterning printing methods such as stencil printing, screen printing, flexographic printing, gravure printing, offset printing, dispenser printing, and inkjet printing. The amount of the copper fine particle dispersion applied to the metal members can be appropriately adjusted depending on the size and type of the metal members to be bonded.

[0065] The bond strength of the bonded body is preferably 20 MPa or more. The bond strength can be measured by the method described in the Examples.

[0066] In addition to the above-mentioned embodiments, the present invention further discloses the following embodiments. <1> A copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 55% by mass or more and 97% by mass or less, The acid value of the polymer B is 20 mgKOH / g or more and 250 mgKOH / g or less, The copper fine particle dispersion, wherein the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycol, a (poly)alkylene glycol derivative, a terpene alcohol, glycerin, and a glycerin derivative. <2> A copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a vinyl-based polymer including a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 60% by mass or more and 94% by mass or less, The acid value of the polymer B is 25 mgKOH / g or more and 230 mgKOH / g or less, the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycols, (poly)alkylene glycol derivatives, terpene alcohols, glycerin, and glycerin derivatives; The boiling point of the solvent C is 180° C. or more and 400° C. or less. <1> The copper fine particle dispersion according to claim 1. <3> A copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a vinyl-based polymer including a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 60% by mass or more and 94% by mass or less, The acid value of the polymer B is 25 mgKOH / g or more and 230 mgKOH / g or less, the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycols, (poly)alkylene glycol derivatives, terpene alcohols, glycerin, and glycerin derivatives; The molecular weight of the solvent C is 60 or more and 600 or less. <1> or <2> The copper fine particle dispersion according to claim 1. <4> A copper microparticle dispersion containing copper nanoparticles A dispersed in a polymer B and a dispersion medium C, the polymer B comprises a vinyl-based polymer including a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment, the monomer (b-1) having a carboxy group contains at least one selected from (meth)acrylic acid and maleic acid, the monomer (b-2) having a polyalkylene glycol segment includes a polyalkylene glycol (meth)acrylate and an alkoxy polyalkylene glycol (meth)acrylate having an alkoxy group having 1 to 18 carbon atoms, The content of the polyalkylene glycol segment in the polymer B is 60% by mass or more and 94% by mass or less, The acid value of the polymer B is 25 mgKOH / g or more and 230 mgKOH / g or less, the dispersion medium C contains at least one selected from the group consisting of (poly)alkylene glycols, (poly)alkylene glycol derivatives, and terpene alcohols; The boiling point of the solvent C is 180° C. or more and 400° C. or less, The molecular weight of the solvent C is 60 or more and 600 or less. <1> ~ <3> 2. The copper fine particle dispersion according to claim 1 . <5> The content of the copper nanoparticles A is 30% by mass or more and 95% by mass or less, The mass ratio of the content of the polymer B to the total content of the copper nanoparticles A and the polymer B [polymer B / (copper nanoparticles A + polymer B)] is 0.0055 or more and 0.025 or less, The content of the dispersion medium C is 4% by mass or more and 60% by mass or less. <1> ~ <4> 2. The copper fine particle dispersion according to claim 1 . <6> The content of the copper nanoparticles A is 50% by mass or more and 91% by mass or less, The mass ratio of the content of the polymer B to the total content of the copper nanoparticles A and the polymer B [polymer B / (copper nanoparticles A + polymer B)] is 0.0055 or more and 0.025 or less, The content of the dispersion medium C is 4% by mass or more and 20% by mass or less. <1> ~ <5> 2. The copper fine particle dispersion according to claim 1 . <7> The content of the polymer B is 0.1% by mass or more and 10% by mass or less. <5> or <6> The copper fine particle dispersion according to claim 1. <8> the content of a vinyl polymer including a constituent unit derived from a monomer (b-1) having a carboxy group and a constituent unit derived from a monomer (b-2) having a polyalkylene glycol segment in the polymer B is 80% by mass or more; the total content of the (poly)alkylene glycol, the (poly)alkylene glycol derivative, the terpene alcohol, the glycerin and the glycerin derivative in the solvent C is 50 mass% or more; <2> ~ <7> 2. The copper fine particle dispersion according to claim 1 . <9> the content of the vinyl polymer including the constituent unit derived from the monomer (b-1) having a carboxy group and the constituent unit derived from the monomer (b-2) having a polyalkylene glycol segment in the polymer B is 95% by mass or more; the total content of the (poly)alkylene glycol, the (poly)alkylene glycol derivative, the terpene alcohol, the glycerin and the glycerin derivative in the solvent C is 95% by mass or more; <2> ~ <7> 2. The copper fine particle dispersion according to claim 1 . <10> The average particle size of the copper nanoparticles A is 105 nm or more and 270 nm or less. <1> ~ <9> 2. The copper fine particle dispersion according to claim 1 . <11> the total content of the structural units derived from the monomer (b-1) and the structural units derived from the monomer (b-2) in the vinyl polymer B is 72 mass% or more; <2> ~ <10> 2. The copper fine particle dispersion according to claim 1 . <12> the content of the structural units derived from the monomer (b-1) in the vinyl polymer B is 3% by mass or more and 35% by mass or less, and the content of the structural units derived from the monomer (b-2) in the vinyl polymer B is 55% by mass or more and 97% by mass or less; <2> ~ <11> 2. The copper fine particle dispersion according to claim 1 . <13> the solvent C contains at least one selected from dipropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight of 180 or more and 500 or less), α-terpineol, and diethylene glycol monobutyl ether, and the total content of the compounds in the solvent C is 95 mass% or more; <1> ~ <12> 2. The copper fine particle dispersion according to claim 1 . <14> Further comprising copper microparticles, the average particle size of the copper microparticles being greater than 0.27 μm and less than or equal to 10 μm; <1> ~ <13> 2. The copper fine particle dispersion according to claim 1 . <15> The content of the copper microparticles is 5% by mass or more and 65% by mass or less. <14> The copper fine particle dispersion according to claim 1. <16> Used to join multiple metal components, <1> ~ <15> 2. The copper fine particle dispersion according to claim 1 . <17> <1> ~ <16> 2. A method for producing a bonded body, comprising a step of interposing the copper fine particle dispersion according to any one of claims 1 to 11 between a plurality of metal members and heating the resulting mixture. <18> The heating temperature in the heating step is 230° C. or less. <17> A method for producing the bonded body according to claim 1. <19> The atmosphere in the heating step is an inert gas atmosphere. <17> or <18> A method for producing the bonded body according to claim 1. <20> The metal member includes at least one selected from the group consisting of a gold substrate, a gold-plated substrate, a silver substrate, a silver-plated metal substrate, a copper substrate, a palladium substrate, a palladium-plated metal substrate, a platinum substrate, a platinum-plated metal substrate, an aluminum substrate, a nickel substrate, a nickel-plated metal substrate, a tin substrate, a tin-plated metal substrate, and a metal portion of an electrically insulating substrate; <17> ~ <19> 13. A method for producing the bonded body according to any one of claims 1 to 12. <21> The joining of the metal members is any one selected from the group consisting of joining a chip component and a circuit board, joining a semiconductor chip and a lead frame or a circuit board, and joining a semiconductor chip that generates high heat and a cooling plate. <17> ~ <20> 13. A method for producing the bonded body according to any one of claims 1 to 12. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples. In the following Production Examples, Examples and Comparative Examples, "parts" and "%" are "parts by mass" and "% by mass" unless otherwise specified. Various physical properties were measured or calculated by the following methods.

[0068] [Measurement of number average molecular weight Mn of polymer B] The measurement was performed by gel permeation chromatography. The measurement sample was prepared by mixing 0.1 g of polymer with 10 mL of eluent in a glass vial, stirring with a magnetic stirrer at 25°C for 10 hours, and filtering with a syringe filter (DISMIC-13HP PTFE 0.2 μm, manufactured by Advantec Toyo Co., Ltd.). The measurement conditions are shown below. GPC equipment: Tosoh Corporation "HLC-8320GPC" Column: Tosoh Corporation "TSKgel SuperAWM-H, TSKgel SuperAW3000, TSKgel guardcolumn Super AW-H" Eluent: N,N-dimethylformamide with phosphoric acid and lithium bromide dissolved at concentrations of 60mmol / L and 50mmol / L, respectively. Flow rate: 0.5mL / min Standard material: Monodisperse polystyrene kit, Tosoh Corporation "PStQuick B (F-550, F-80, F-10, F-1, A-1000), PStQuick C (F-288, F-40, F-4, A-5000, A-500)"

[0069] [Measurement of acid value of polymer B] The acid value of polymer B was measured in accordance with JIS K0070-1992 (potentiometric titration method), except that the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070 to a mixed solvent of acetone and toluene (acetone:toluene=4:6 (volume ratio)).

[0070] [Calculation of the content of polyalkylene glycol segments in polymer B] The polyalkylene glycol segment content of Polymer B was calculated by multiplying the monomer mass part in Table 1 and the polyalkylene glycol segment ratio in Table 2 described below.

[0071] [Average particle size of copper nanoparticles A and copper microparticles] Scanning electron microscope (SEM) images of copper nanoparticles A and copper microparticles were taken using a scanning electron microscope (Hitachi High-Tech Corporation, field emission scanning electron microscope: S-4800). The magnification was determined according to the particle size of the particles, and images were taken at magnifications ranging from 5,000x to 150,000x. The SEM images were analyzed using image analysis software ImageJ (National Institutes of Health, USA) to determine the particle sizes of 100 or more particles per sample, and the arithmetic mean value of these was used as the average particle size of copper nanoparticles A and copper microparticles.

[0072] [Calculation of polymer mass ratio [polymer B / (copper nanoparticle A + polymer B)]] Using a thermogravimetric and differential thermal analyzer (TG / DTA) (Hitachi High-Tech Science Corporation, product name: STA7200RV), 10 mg of the sample (dried powder of copper nanoparticles A containing polymer B) was weighed into an aluminum pan, and the temperature was increased from 35 ° C to 550 ° C at a heating rate of 10 ° C / min under a nitrogen flow of 50 mL / min, and the mass loss was measured. The mass loss from 35 ° C to 550 ° C was the mass of polymer B, and the remaining mass at 550 ° C was the mass of copper nanoparticles A, and the polymer mass ratio [polymer B / (copper nanoparticles A + polymer B)] was calculated by the following formula. Polymer mass ratio = (mass loss from 35°C to 550°C) / (mass loss from 35°C to 550°C + remaining mass at 550°C)

[0073] (Production of Polymer B) Manufacturing Example 1 In a 1000mL four-necked round-bottom flask equipped with a thermometer, two 100mL nitrogen bypass dropping funnels, and a reflux device, 20.0g of ethanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent) was placed, and the internal temperature of the flask was heated to 80°C in an oil bath, followed by 10 minutes of nitrogen bubbling. Next, 15.3g of methacrylic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent), 17.2g of methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent), 67.5g of methoxypolyethylene glycol (EO23 mol) methacrylate (NOF Corporation, "PME-1000"), 1.0g of 3-mercaptopropionic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent), and 28.7g of ethanol were dissolved in a polybeaker and placed in the dropping funnel (1). Separately, 51.3 g of ethanol and 1.3 g of 2,2'-azobis(2,4-dimethylvaleronitrile) ("V-65" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., polymerization initiator) were dissolved in a polybeaker and placed in the dropping funnel (2). Next, the mixtures in the dropping funnels (1) and (2) were simultaneously dropped into the flask over 90 minutes. Thereafter, the internal temperature of the flask was raised to 90°C, and stirring was continued for another hour to terminate the reaction. The resin solution was freeze-dried using a freeze dryer (Tokyo Rika Kikai Co., Ltd., model: FDU-2110) equipped with a dry chamber (Tokyo Rika Kikai Co., Ltd., model: DRC-1000) under drying conditions (freezing at -25°C for 1 hour, vacuum at -10°C for 9 hours, vacuum at 25°C for 5 hours. Vacuum degree 5 Pa) to obtain bone-dried polymer B-1 (methacrylic acid / methyl methacrylate / methoxypolyethylene glycol (EO23 mol) methacrylate polymer, acid value: 100 mg KOH / g, Mn: 8,000).

[0074] Manufacturing Examples 2-22 Polymers B-2 to B-22 were obtained by the same production method as in Production Example 1, except that the monomer compositions shown in Table 1 were used instead. Details of the monomers used are shown in Table 2.

[0075] [Table 1-1]

[0076] [Table 1-2]

[0077] [Table 2]

[0078] (Synthesis of dry copper nanoparticle powder) Synthesis Example 1 Into a 2 L beaker, 88.4 g of copper sulfate pentahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent) was added as a copper raw material compound, 0.7 g of Polymer B-1 obtained in Production Example 1 in an absolute dry state as a dispersant, and 1000 g of ion-exchanged water were added, and the mixture was stirred at 40°C using a magnetic stirrer until it became visually transparent, thereby obtaining a mixed liquid. Next, 17.8 g of hydrazine monohydrate (special grade reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) placed in a 50 mL dropping funnel was dropped into the mixture over 60 minutes at 25° C. Thereafter, the reaction solution was stirred for 5 hours while controlling the temperature at 40° C. in an oil bath, and then air-cooled to obtain a reddish-brown dispersion containing dispersed copper nanoparticles. The entire amount of the obtained dispersion was put into a dialysis tube (manufactured by REPLIGEN, product name: Spectra / Pore 6, dialysis membrane: regenerated cellulose, molecular weight cutoff (MWCO) = 50K), and the top and bottom of the tube were sealed with a closure. This tube was immersed in 5 L of ion-exchanged water in a 5 L glass beaker, and the water temperature was kept at 20 to 25 ° C and stirred for 1 hour. After that, the ion-exchanged water was replaced with the entire amount every hour. Sampling was performed before replacing the ion-exchanged water, and when the conductivity of the dispersion of copper nanoparticles became 7 mS / m or less, dialysis was terminated to obtain a dispersion of copper nanoparticles. The conductivity was measured by diluting with ion-exchanged water to adjust the copper concentration to 1%. The refined copper nanoparticle dispersion was freeze-dried using a freeze dryer (Tokyo Rikakikai Co., Ltd., model: FDU-2110) equipped with a dry chamber (Tokyo Rikakikai Co., Ltd., model: DRC-1000) to obtain 21.3 g of copper nanoparticles A-1 containing polymer B-1. The drying conditions were freezing at -25 ° C for 1 hour, drying at -10 ° C for 9 hours under reduced pressure at 5 Pa, and further drying at 25 ° C for 5 hours under reduced pressure at 5 Pa to obtain a dried powder of copper nanoparticles A-1 containing polymer B-1. The obtained copper nanoparticles A-1 had an average particle size of 160 nm and a polymer mass ratio of 0.011. The results are shown in Table 3.

[0079] Synthesis Examples 2-22 Each copper nanoparticle dry powder was obtained in the same manner as in Synthesis Example 1, except that the dispersant was changed to Polymers B-2 to B-22 shown in Table 3. The average particle size and polymer mass ratio of each of the obtained copper nanoparticles are shown in Table 3.

[0080] [Table 3]

[0081] Example 1 (Preparation of copper fine particle dispersion) 0.5 g of dipropylene glycol (Fujifilm Wako Pure Chemical Industries, Ltd., first-class reagent), 0.5 g of tetraethylene glycol (Fujifilm Wako Pure Chemical Industries, Ltd., first-class reagent), and 9.0 g of dried powder of copper nanoparticles A-1 containing polymer B-1 obtained in Synthesis Example 1 were added to an agate mortar and kneaded until the dried powder was no longer visible to the naked eye, and the resulting mixture was transferred to a plastic bottle. The sealed plastic bottle was stirred for 2000 min using a rotation-revolution type stirring device (Thinky Corporation, Planetary Vacuum Mixer ARV-310). -1 The mixture was stirred at 2000 rpm for 5 minutes to obtain copper fine particle dispersion 1.

[0082] (Manufacturing of Joints) Using the obtained copper particulate dispersion 1, a bonded body was produced according to the following method. First, a stainless steel metal mask (thickness: 150 μm) having three rows of 6 mm × 6 mm square openings was placed on a 30 mm × 30 mm copper plate (total thickness: 1 mm), and the copper microparticle dispersion was applied to the copper plate by stencil printing using a metal squeegee. Then, it was dried at 120 ° C. for 10 minutes in air on a Shamal hot plate (HHP-441, manufactured by AS ONE Corporation). Then, a silicon chip (thickness: 400 μm) of 5 mm × 5 mm was prepared by sputtering titanium, nickel, and gold in this order, and the silicon chip was placed on the applied copper microparticle dispersion so that the gold was in contact with the copper microparticle dispersion. As a result, a laminate was obtained in which the copper plate, the copper microparticle dispersion, and the silicon chip were laminated in this order. The obtained laminate was sintered by the following method to obtain a bonded body. First, the laminate was set in a pressure sintering machine (HTM-1000, manufactured by Meisho Kiko Co., Ltd.), and nitrogen was flowed into the furnace at 500 mL / min to replace the air in the furnace with nitrogen. Then, the temperature of the heating heads was raised to 200°C over 10 minutes while pressurizing the laminate at 20 MPa using the upper and lower heating heads. After the temperature increase, the laminate was sintered by holding at 200°C for 150 seconds to obtain a bonded body. After sintering, the heating heads were water-cooled at -60°C / min, and the bonded body was taken out into the air at 100°C or less.

[0083] Examples 2 to 23, Comparative Examples 1 to 5 The same procedures as in Example 1 were carried out except that the composition of the copper particulate dispersion was changed to the composition shown in Table 4, thereby obtaining copper particulate dispersions and joined bodies of Examples 2 to 23 and Comparative Examples 1 to 5, respectively.

[0084] The raw materials used in the production of the copper microparticle dispersion are shown below. MA-C025 (copper microparticles, manufactured by Mitsui Mining & Smelting Co., Ltd., particle size 5.0 μm) 1050Y (copper microparticles, manufactured by Mitsui Mining & Smelting Co., Ltd., particle size 0.8 μm) Dipropylene glycol (DPG, Fujifilm Wako Pure Chemical Industries, first-class reagent) Tetraethylene glycol (TEG, Fujifilm Wako Pure Chemical Industries, first-class reagent) PEG400 (Fujifilm Wako Pure Chemical Industries, first-class reagent, polyalkylene glycol 400) α-Terpineol (Fujifilm Wako Pure Chemical Industries, special grade reagent) Diethylene glycol monobutyl ether (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent)

[0085] The copper particulate dispersions and joined bodies obtained in Examples 1 to 23 and Comparative Examples 1 to 5 were used to carry out the following evaluations.

[0086] <Evaluation> [Bonding strength of joints] The bond strength of the bonded bodies was measured according to the following procedure. Using a universal bond tester (Prospector, manufactured by Nordson Advanced Technology Co., Ltd.), the silicon chip of the bonded body was pushed horizontally at a test speed of 5 mm / min and a shear height of 50 μm to measure the die shear strength of the bonded body. Three pieces of each bonded body were tested, and the average value of the values ​​obtained by measuring the three bonded bodies was taken as the bond strength of the bonded body.

[0087] [Storage stability of copper particle dispersion] The copper particulate dispersion was stored for one month under conditions of 25° C. and 50% humidity, and then the bonding strength of the bonded body was measured in the same manner as described above. The results are shown in Table 4.

[0088] [Table 4]

[0089] As can be seen from Table 4, the copper microparticle dispersions of Examples 1 to 23 had improved bonding strength even when pressurized and fired at 200°C under nitrogen, and the bond strength of the resulting bonded bodies was good even after storage for one month, compared to the copper microparticle dispersions of Comparative Examples 1 to 5. From the above, it can be seen that the copper microparticle dispersions of the present invention have improved bonding strength and good storage stability even when fired under nitrogen at 200°C.

Claims

1. Contains copper nanoparticles A and polymer B, the polymer B comprises a structural unit of a monomer (b-1) having a carboxy group and a structural unit of a monomer (b-2) having a polyalkylene glycol segment, The content of the polyalkylene glycol segment in the polymer B is 55% by mass or more and 97% by mass or less, The acid value of the polymer B is 20 mgKOH / g or more and 250 mgKOH / g or less.

2. The copper nanoparticle dry powder according to claim 1, wherein the content of the copper nanoparticles A is 30% by mass or more and 95% by mass or less.

3. The mass ratio of the content of the polymer B to the total content of the copper nanoparticles A and the polymer B [polymer B / (copper nanoparticles A + polymer B)] is 0.0055 or more and 0.025 or less. The copper nanoparticle dry powder according to claim 1 or 2.

4. The copper nanoparticle dry powder according to any one of claims 1 to 3, wherein the average particle size of the copper nanoparticles A is 105 nm or more and 270 nm or less.

5. The copper nanoparticle dry powder according to any one of claims 1 to 4, which is used for joining a plurality of metal members.

Citation Information

Patent Citations

  • Joining agent for inorganic stock, and joined body of inorganic stock

    JP2010150653A

  • Pasty metal particulate composition, method for manufacturing solid metal or solid metal alloy, method for joining metallic members, method for manufacturing print wire board, and method for manufacturing bump for connecting electric circuits

    JP2014111800A

  • Metal dispersions with enhanced stability

    JP2018535321A

  • Dispersion of metal fine particles

    JP2020105624A